(untitled) (Tidsskrift for Praktisk Teologi, 2022)
This article explores the frames and topics of youth pastoral care based on an online survey with 314 priests, deacons, catechists and other pastoral care providers in the Church of Norway. The pastoral care conversations were most often spontaneously established in arenas for youth activities, but some appointments were also done in advance. In the survey, 50 different themes with set answer alternatives from never to very often were listed. Factor analyses generated five clusters of themes related torelationships and identity, faith and meaning, trauma and shame, sex and drugs, and personal and social difficulties. The study describes how youth pastoral care conversations cover a broad specter, which mirrors specific challenges among adolescents, indicating that this part of youth ministry might be of great importance. However, more knowledge is needed about the articulation and processing of these themes in the dialogues between the young person and the pastoral care provider, and about the adolescents’ own experiences and assessments of these conversations.